2011
DOI: 10.1002/ijc.26376
|View full text |Cite
|
Sign up to set email alerts
|

ABO blood group, hepatitis B viral infection and risk of pancreatic cancer

Abstract: Little is known about the role of association between ABO blood type and risk of pancreatic cancer develops through effects on hepatitis B viral (HBV) infection. Our study aimed to determine whether joint ABO blood type and HBV infection could increase the risk for pancreatic cancer. A total of 645 patients with pancreatic adenocarcinoma and 711 age-and sex-matched individuals who had nonmalignant diseases treated at the Sun Yat-sen University Cancer Center in China were retrospectively analyzed. Blood samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
99
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 116 publications
(100 citation statements)
references
References 45 publications
1
99
0
Order By: Relevance
“…After review, two studies were excluded with the following reasons: a study of HCV infection (El-Serag et al, 2009); a case report (Yoo et al, 2009). Thus, eight articles met the inclusion criteria (de Gonzalez et al, 2008;Hassan et al, 2008;Gordon et al, 2009;Iloeje et al, 2009;Hong et al, 2010;Zhu et al, 2011;Ben et al, 2012;Wang et al, 2012), six of these studies were conducted only in East Asia (de Gonzalez et al, 2008;Iloeje et al, 2009;Hong et al, 2010;Zhu et al, 2011;Ben et al, 2012;Wang et al, 2012) and two in USA (Hassan et al, 2008;Gordon et al, 2009).…”
Section: Literature Search and Studies Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…After review, two studies were excluded with the following reasons: a study of HCV infection (El-Serag et al, 2009); a case report (Yoo et al, 2009). Thus, eight articles met the inclusion criteria (de Gonzalez et al, 2008;Hassan et al, 2008;Gordon et al, 2009;Iloeje et al, 2009;Hong et al, 2010;Zhu et al, 2011;Ben et al, 2012;Wang et al, 2012), six of these studies were conducted only in East Asia (de Gonzalez et al, 2008;Iloeje et al, 2009;Hong et al, 2010;Zhu et al, 2011;Ben et al, 2012;Wang et al, 2012) and two in USA (Hassan et al, 2008;Gordon et al, 2009).…”
Section: Literature Search and Studies Characteristicsmentioning
confidence: 99%
“…There were a total of 302420 individuals in the included eight studies. In most of the studies (de Gonzalez et al, 2008;Hassan et al, 2008;Gordon et al, 2009;Zhu et al, 2011;Ben et al, 2012;Wang et al, 2012), pancreatic cancer was diagnosed according the histology. In other studies (Iloeje et al, 2009;Hong et al, 2010), pancreatic cancer is confirmed by histology or diagnosed by symptoms, signs and more than two types of imaging tools.…”
Section: Literature Search and Studies Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations